Evaluation of Inaccuracy Analysis of Returning Inpatient Medical Record Documents at “X” Hospital in Malang City - Ratna Wardani; Fita Rusdian Ikawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
This study uses a qualitative method, the data collection is in the form of interview and observation techniques on medical record Assembling officers, registration officers, verification officers, distribution officers and nurses at RS